The clinical characteristics of Hirayama disease in females - Hongwei Wang; Wei Lei; Ye Tian; Jianwei Wu; Xiaosheng Ma; Feizhou Lyu; Xinlei Xia; Jingjuan Liang; Jianyuan Jiang; Hongli Wang (Neurología (English Edition))
Introduction: To characterize Hirayama disease in female patients, and increase awareness among clinicians regarding the specifics of this disease. Methods: Baseline data, clinical manifestations, characteristics of cervical-flexion magnetic resonance imaging, and electromyography were collected and compared among females and males with Hirayama disease. In addition, the literature on Hirayama disease in females up to October, 2021 was searched in PubMed and the relevant data were compared with the data from our study. Results: Twenty female and 40 male patients were included in this study. The average ages of onset and menarche were 14.65 and 12.75 years old. All patients suffered from muscular weakness and atrophy of the upper limb(s), with flattening and/or atrophy of the lower cervical spinal cords in cervical-flexion magnetic resonance imaging, and neurogenic patterns in the atrophic muscles as determined using electromyography. The age of onset in females was about 2 years later than the age of menarche, and the age of onset in females was 2 years earlier than that in males. There were no obvious differences in clinical presentation between males and females. Discussion: Although females presented with Hirayama disease two years earlier than males, no other clinical differences were observed. Hirayama disease is likely associated with growth and development in puberty, and early identification, regardless of whether patients are male or female, is critical to optimizing prognosis. Resumen: Introducción: Para detallar la enfermedad de Hirayama en pacientes femeninos y promover la conciencia entre los médicos con respecto a los detalles específicos de esta enfermedad. Metodología: Datos de referencia, manifestaciones clínicas, características de las imágenes de resonancia magnética de flexión cervical y la electromiografía fueron recopilados y comparados entre mujeres y hombres con la enfermedad de Hirayama. Aunado a esto, la literatura sobre la enfermedad de Hirayama en mujeres hasta octubre de 2021 fue revisada en PubMed y la información relevante fue comparada con los datos de nuestro estudio. Resultado: 20 pacientes femeninos y 40 pacientes masculinos fueron incluidos en este estudio. Las edades promedio de inicio y menarquia fueron 14, 65 y 12, 75 años. Todos los pacientes padecían debilidad muscular y atrofia de las extremidades superiores, con aplanamiento y/o atrofia de la médula espinal cervical inferior en imágenes de resonancia magnética de flexión cervical y patrones neurogénicos en los músculos atrofiados como fue determinado usando electromiografía. La edad de inicio en las mujeres fue aproximadamente 2 años más tarde que la edad de la menarquia, y la edad de inicio en las mujeres fue 2 años antes que en los hombres. No hubo diferencias obvias en la presentación clínica entre hombres y mujeres. Discusión: Aunque las mujeres presentaron la enfermedad de Hirayama dos años antes que los hombres, no se observaron otras diferencias clínicas. Es probable que la enfermedad de Hirayama sea asociada con el crecimiento y desarrollo en la pubertad, y la identificación temprana, independientemente de si los pacientes son hombres o mujeres, es fundamental para optimizar el pronóstico médico.